Impact of Watershed Management Technology on Resource Use, Production and Employment in Dry Regions of South-Eastern Rajasthan: A Case Study of Chhajawa Watershed - Dhyani, B L; Singh, K D; Prasad, S N; Singh, Ratan (Annals of Arid Zone, 2016)
Chhajawa watershed is one of the 47 model watersheds taken up by Indian Council of Agricultural Research in 1983 to verify the results ofthree experimental watersheds implemented by it during 1970s. Watershed represents agro-climatic and agricultural resource use pattern of south-eastern Rajasthan. Watershed plan was prepared by Central Soil and Water Conservation Research and Training Institute, Research Centre, Kota, and implemented by State Soil Conservation Department during 1986-1989. After eight years of completion of the project, a study was taken up to judge the efficiency of watershed management technologies on sustainable agricultural production and gainful employment generation with environmental security. The primary data from 50 farm families and time series (secondary). data from records of the watershed were collected and analyzed using budgeting and functional approach. The study revealed that watershed management project at Chhajawa had improved resources availability to the farmers, increased resource-use efficiency and total production from arable and non-arable land, as well as animal base after the project. The program had significantly increased employment opportunities in the watershed. Irrigated area, capital recovery factor to investment on soil and water . conservation technologies and cropping intensity were found to be the most important determinants for enhancement of regular employment opportunities in the watershed.